Continuous hydrogen production from food waste by anaerobic digestion (AD) coupled single-chamber microbial electrolysis cell (MEC) under negative pressure. (15th February 2020) - Huang, Jingjing; Feng, Huajun; Huang, Lijie; Ying, Xianbin; Shen, Dongsheng; Chen, Ting; Shen, Xiajuan; Zhou, Yuyang; Xu, Yingfeng
Graphical abstract: Highlights: MEC with FW as substrate can obtain high H2 recovery under negative pressure. MEC combined with AD enables a hydrogen production rate of 3.48 L/L/d. MEC reactor for continuous hydrogen production by increasing acid conversion. MEC can successfully increase the degree of solid reduction. Abstract: Increased generation of food waste (FW) poses significant risks to the social environment, and therefore it is critical that efficient technology be developed for effective waste valorization. This study used an integrated reactor to combine single-chamber microbial electrolysis cell (MEC) treatment and anaerobic digestion (AD) to achieve efficient hydrogen recovery using FW as substrate. Hydrogen production during continuous AD-MEC operation (511.02 ml H2 g −1 VS) was higher than that achieved by AD (49.39 ml H2 g −1 VS). The hydrogen recovery and electrical energy recovery in AD-MEC were as high as 96% and 238.7 ± 5.8%, respectively. To explore the mechanism of hydrogen production increase, the main components of FW [lipids, volatile fatty acids (VFAs), carbohydrates, and protein] were analyzed to investigate the utilization of organic matter. Compared with AD treatment, the removal rates of carbohydrates and proteins in the soluble phase in AD-MEC were increased by 4 times and 2.3 times, respectively. The removal of VFAs by AD-MEC was increased by 4.7 times, which indicated that the AD reactor coupled with MEC technology improved the utilization of the main organic components and thus increased hydrogen production. This study demonstrates the possibilities of reducing FW quantities along with the production of bio-hydrogen.